NMR spectroscopy of filtered serum of prostate cancer: A new frontier in metabolomics. Issue 12 (16th May 2016) - Kumar, Deepak; Gupta, Ashish; Mandhani, Anil; Sankhwar, Satya Narain
Abstract : BACKGROUND: To address the shortcomings of digital rectal examinations (DRE), serum prostate‐specific antigen (PSA), and trans‐rectal ultrasound (TRUS) for precise determination of prostate cancer (PC) and differentiation from benign prostatic hyperplasia (BPH), we applied 1 H‐nuclear magnetic resonance (NMR) spectroscopy as a surrogate tactic for probing and prediction of PC and BPH. METHODS: The study comprises 210 filtered sera from suspected PC, BPH, and a healthy subjects' cohort (HC). The filtered serum approach delineates to identify and quantify 52 metabolites using 1 H NMR spectroscopy. All subjects had undergone clinical evaluations (DRE, PSA, and TRUS) followed by biopsy for Gleason score, if needed. NMR‐measured metabolites and clinical evaluation data were examined separately using linear multivariate discriminant function analysis (DFA) to probe the signature descriptors for each cohort. RESULTS: DFA indicated that glycine, sarcosine, alanine, creatine, xanthine, and hypoxanthine were able to determine abnormal prostate (BPH + PC). DFA‐based classification presented high precision (86.2% by NMR and 68.1% by clinical laboratory method) in discriminating HC from BPH + PC. DFA reveals that alanine, sarcosine, creatinine, glycine, and citrate were able to discriminate PC from BPH. DFA‐based categorization exhibited high accuracy (88.3% by NMR and 75.2% by clinical laboratory method) to differentiate PC from BPH. CONCLUSIONS: 1 H NMR‐based metabolic profiling of filtered‐serum sample appears to be assuring, swift, and least‐invasive for probing and prediction of PC and BPH with its signature metabolic profile. This novel technique is not only on a par with histopathological evaluation of PC determination but is also comparable to liquid chromatography‐based mass spectrometry to identify the metabolites. Prostate 76:1106–1119, 2016 . © 2016 Wiley Periodicals, Inc.